THE ROLE OF MODERN TEACHING METHODS IN LANGUAGE EDUCATION - Mamanazarova Rayhona Nurbek qizi (TADQIQOTLAR, 2025)
Abstract In the 21 st century, language teaching has shifted from teacher-centered instruction to learner-centered approaches that emphasize communication, collaboration, and creativity. The process of globalization, the growth of international communication, and the widespread use of technology have significantly influenced the way languages are taught and learned. Traditional approaches, such as the Grammar-Translation Method or the Audio-Lingual Method, which focused primarily on rote memorization and grammatical accuracy, are no longer sufficient to meet the communicative needs of modern learners. Today, education systems emphasize interaction, creativity, and learner autonomy as the foundation of effective language learning. Modern teaching methods in language education aim to create a learner- centered environment where students actively participate in the learning process rather than passively receive information.